2019
DOI: 10.1002/ccd.28325
|View full text |Cite
|
Sign up to set email alerts
|

A risk score to predict postdischarge bleeding among acute coronary syndrome patients undergoing percutaneous coronary intervention: BRIC‐ACS study

Abstract: Background Dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) prevents ischemic events while increasing bleeding risk. Real‐world‐based metrics to accurately predict postdischarge bleeding (PDB) occurrence and its potential impact on postdischarge major cardiovascular event (MACE) remain undefined. This study sought to evaluate the impact of PDB on MACE occurrence, and to develop a score to predict PDB risk among Chinese acute coronary syndrome (ACS) patients after PCI. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
4
9
1
1
Order By: Relevance
“…Consistent with other studies, the gut 15 , 21 , 28 was the most frequent identifiable source of bleeding in our study. It was also the most common location for a second bleeding event, regardless of the location of the first site.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies, the gut 15 , 21 , 28 was the most frequent identifiable source of bleeding in our study. It was also the most common location for a second bleeding event, regardless of the location of the first site.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the findings of previous studies, 32,33 gastrointestinal hemorrhage was the most common type of clinically relevant bleeding in our study. Furthermore, it occurred more frequently in patients switched to ticagrelor than in those continued on clopidogrel.…”
Section: Discussionsupporting
confidence: 93%
“…Our study shares similar results with another real-world observational research, the BRIC-ACS study, 33 in which ticagrelor was strongly associated with a higher risk of BARC Type 2/3/5 bleeding but not with a lower risk of MACE in comparison to clopidogrel.…”
Section: Clinical Outcomessupporting
confidence: 90%
“…The database included 31 centers with 7,862 Chinese adult ACS patients who underwent PCI, and these patients were discharged from hospital between January 2014 and October 2017. Patient data were obtained from the BRIC-ACS(I) study (2,381 patients) (6), COSTIC study (4,447 patients) (10), and cases from the Sixth Medical Center of PLA General Hospital PCI patient database (1,034 patients). The data for the patients who underwent PCI with second-or thirdgeneration drug-eluting stent (DES) implantation, and were treated either with clopidogrel or ticagrelor plus aspirin for 12 months of follow-up were included in this real-world study.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…However, the pharmacological limitations associated with clopidogrel DAPT have led to the development of novel reversible P2Y12 receptor antagonists (5). According to the current guidelines based on previously conducted clinical trials [PLATO trial (3)], the use of ticagrelor as a novel potent P2Y12 inhibitor is recommended after PCI for 12 months to reduce coronary thrombosis and mortality in patients with ACS (6). Studies have shown that DAPT reduces the risk of stent-related and spontaneous recurrent ischemic events in patients with ACS undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%